Rare damage to the tendons of the posterior thigh muscle group. Clinical case - A. V. Mironov; V. S. Mironov; V. V. Shalin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Hamstring tendon injury is a rare high-energy injury.The aim of the work is to demonstrate a rare clinical case of simultaneous damage to the distal tendon of the semimembranous muscle and the distal tendon of the biceps femoris.Object and methods. The patient is 55 years old, fell on the ice and sat in the "splits" position. Immediately after the injury, there was a sharp pain, the absence of active flexion of the right shin. She was treated conservatively. However, the pronounced pain syndrome and the lack of active movements forced the patient to do an MRI and consult a traumatologist.Results and discussion. After performing an MRI and examination by a traumatologist, damage to the distal tendons of the semi-webbed and biceps femoral muscles was diagnosed. Surgical interventions were performed – tendon suture and tenodesis. Immobilization with a sharshnir splint with a bending angle of 80 degrees. After immobilization, a dosed extension of the knee joint with a hinge system with a frequency of 5 degrees per day was performed for 6 weeks. After carrying out a full complex of medical rehabilitation using physiotherapy and the Arthromot apparatus, the volume of movements is 0/0/180.Conclusion. Early surgical treatment and competent rehabilitation measures allow you to fully restore the lost functions. Even with such rare injuries.